KÓRKEM ÁDEBIY TILDE QARATPALARDÍŃ STILLIK QOLLANÍLÍWÍ - Allanazarov, Esbergen Esbosınovish; Esbergenova, Baǵdagul Perdebaevna (SCIENCE and SOCIETY, 2026)
In the article, one of the linguistic unic of our language is devoted to the event of the use of leksem s unic in the artistic language. In the works of X.Dawletnazarov, some details are given concerning the peculiarities of the meaning of the word in use.